Main symptoms associated to the catastrophizing in women with fibromyalgia and migraine - Barros, Amanda de Oliveira Freire (2020)
ObjectiveTo evaluate the main symptoms associated catastrophizing in women with fibromyalgia and migraine.MethodologyWe conducted an observational study with 26 women diagnosed with both fibromyalgia and migraine, aged between 30 and 60 years (46±8 years). The Pain Catastrophizing Scale was applied as a cut-of point =30, dividing the volunteers in groups with (n=18) and without catastrophizing (n=8). We assessed the quality of sleep (Pittsburgh sleep quality index), the presence of depression and anxiety (Becks depression and anxiety inventories), the quality of life perception (Fibromyalgia impact questionnaire-revised), the disability due to migraine (Migraine disability assessment) and the level of physical activity (International physical activity questionnaire).ResultsThe time of fibromyalgia did not difer (p=0.80) between the group with (8.54±4.88) and without catastrophizing (10.04±3.47). The Fibromyalgia impact questionnaire-revised scores were significantly higher (p=0.01) among women with catastrophizing (78±12.6) than those without (56.6±22.3). There was no diference between the groups (p>0.05) in relation to the other outcomes evaluated.ConclusionThe presence of catastrophizing in women with fibromyalgia and migraine are associated with a worse perception of quality of life. a worse perception of quality of life.